2019
DOI: 10.1001/jamacardio.2018.4635
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation

Abstract: IMPORTANCE Increased free thyroxine (FT 4 ) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear.OBJECTIVE To evaluate the potential direct involvement of thyroid traits on AF. DESIGN, SETTING, AND PARTICIPANTS Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry.EXPOSURES Genomewide significant variants were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 41 publications
9
61
0
Order By: Relevance
“…This is in line with the results of observational studies which have shown that AF is a major risk factor for stroke, increasing stroke risk up to five-fold (44). Our findings are also in line with recent studies showing that subjects with a genetically predicted higher TSH level have a lower risk of AF (40). While multiple pathophysiological pathways might be theoretically involved in the effect of thyroid function on stroke, we demonstrated that AF has a major role in mediating the effect of TSH within the reference range on the stroke risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with the results of observational studies which have shown that AF is a major risk factor for stroke, increasing stroke risk up to five-fold (44). Our findings are also in line with recent studies showing that subjects with a genetically predicted higher TSH level have a lower risk of AF (40). While multiple pathophysiological pathways might be theoretically involved in the effect of thyroid function on stroke, we demonstrated that AF has a major role in mediating the effect of TSH within the reference range on the stroke risk.…”
Section: Discussionsupporting
confidence: 93%
“…The observed causal effect in the unadjusted analyses was independent of BMI, T2D, lipids, BP, HR and educational attainment which was used as a surrogate for socio-economic status (STable 10A, Fig 2). To further assess the effect of TSH on the risk of stroke via AF, we investigated whether the known effect of TSH on AF (40) is mediated by any risk factors. Multivariable MR analyses did not implicate BP, lipids, CAD, or T2D as possible mediators of the observed causal effect of TSH levels on AF risk (STable 11).…”
Section: Mediation Analysesmentioning
confidence: 99%
“…The remarkable HW departure found in TPO, along with the frequency differences between the groups, fortifies our results. Accordingly, other genetic determinants within the TPO, as in other genes involved in the thyroid function, have shown association with cardiovascular risk, suggesting a genetic influence through TH levels [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…The strongest association was found for AF/flutter. The study of Ellervik et al also included fT4 and fT3 in their analysis. In addition to confirming the findings of Salem et al, they reported a significant association between AF and fT3:fT4 ratio but not fT4 alone.…”
Section: Discussionmentioning
confidence: 99%